2021
DOI: 10.1038/s41421-020-00239-w
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study for gut metagenome in Chinese adults illuminates complex diseases

Abstract: The gut microbiome has been established as a key environmental factor to health. Genetic influences on the gut microbiome have been reported, yet, doubts remain as to the significance of genetic associations. Here, we provide shotgun data for whole genome and whole metagenome from a Chinese cohort, identifying no <20% genetic contribution to the gut microbiota. Using common variants-, rare variants-, and copy number variations-based association analyses, we identified abundant signals associated with the gu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 69 publications
5
64
1
Order By: Relevance
“…in China. The protocols for blood and oral collection, as well as the whole genome and metagenomic sequencing were similar to our previous literature 5,23,48 . For blood sample, DNA was extracted using MagPure Buffy Coat DNA Midi KF Kit (no.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…in China. The protocols for blood and oral collection, as well as the whole genome and metagenomic sequencing were similar to our previous literature 5,23,48 . For blood sample, DNA was extracted using MagPure Buffy Coat DNA Midi KF Kit (no.…”
Section: Methodsmentioning
confidence: 87%
“…3,932 (2,017 tongue dorsum and 1,915 saliva) oral samples from this cohort were newly collected for whole metagenomic sequencing between 2017 to 2018 ( Supplementary Table 1 ). The protocols for blood and oral collection, as well as the whole genome and metagenomic sequencing were similar to our previous literature 5,23,42 . For blood sample, DNA was extracted using MagPure Buffy Coat DNA Midi KF Kit (no.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…In our gene-level analysis using the PC-adjusted KRV, the LCT gene is nominally significant based on the unweighted UniFrac kernel (p-value = 0.013), but not significant at the genome-wide level. In addition, we have examined the significance of 63 previously reported genes that harbor variants associated with microbiome beta-diversity [10,12,14,39,40] (Supplementary Table S3). orating the role of immunity-related genes in shaping gut microbiota.…”
Section: Application Of Covariate-adjusted Krv To Hchs/solmentioning
confidence: 99%
“…These approaches still test one variant at a time and are subject to a stringent genome-wide significance threshold. Studies using the above approaches have identified loci within genes involved in immunity [6,12], vitamin metabolism [10] and complex diseases such as type 2 diabetes [14]. In our study, we aim to further improve statistical power with a novel approach and bring more discoveries from microbiome GWAS.…”
Section: Introductionmentioning
confidence: 99%